Answer:
![Remainder = 3](https://tex.z-dn.net/?f=Remainder%20%3D%203)
Step-by-step explanation:
Given
![1\ |\ 1\ \ 2\ \ -3\ \ 3](https://tex.z-dn.net/?f=1%5C%20%7C%5C%201%5C%20%5C%202%5C%20%5C%20-3%5C%20%5C%203)
Required
Determine the remainder
Write down the first digit i.e. 1. So, we have:
![1\ |\ 1\ \ 2\ \ -3\ \ 3](https://tex.z-dn.net/?f=1%5C%20%7C%5C%201%5C%20%5C%202%5C%20%5C%20-3%5C%20%5C%203)
--------------------------------
![|\ 1](https://tex.z-dn.net/?f=%7C%5C%201)
Multiply that 1 by the divisor (1) i.e. ![1 * 1 = 1](https://tex.z-dn.net/?f=1%20%2A%201%20%3D%201)
Write down the result under the next digit i.e. (under 2)
![1\ |\ 1\ \ 2\ \ -3\ \ 3](https://tex.z-dn.net/?f=1%5C%20%7C%5C%201%5C%20%5C%202%5C%20%5C%20-3%5C%20%5C%203)
![1](https://tex.z-dn.net/?f=1)
--------------------------------
![|\ 1](https://tex.z-dn.net/?f=%7C%5C%201)
Sum 2 and 1 i.e ![2 + 1 = 3](https://tex.z-dn.net/?f=2%20%2B%201%20%3D%203)
![1\ |\ 1\ \ 2\ \ -3\ \ 3](https://tex.z-dn.net/?f=1%5C%20%7C%5C%201%5C%20%5C%202%5C%20%5C%20-3%5C%20%5C%203)
![1](https://tex.z-dn.net/?f=1)
--------------------------------
Multiply that 3 by the divisor (1) i.e. ![1 * 3 = 3](https://tex.z-dn.net/?f=1%20%2A%203%20%3D%203)
Write down the result under the next digit i.e. (under -3)
![1\ |\ 1\ \ 2\ \ -3\ \ 3](https://tex.z-dn.net/?f=1%5C%20%7C%5C%201%5C%20%5C%202%5C%20%5C%20-3%5C%20%5C%203)
![3](https://tex.z-dn.net/?f=3)
--------------------------------
Sum -3 and 3 i.e ![-3 + 3 = 0](https://tex.z-dn.net/?f=-3%20%2B%203%20%3D%200)
![1\ |\ 1\ \ 2\ \ -3\ \ 3](https://tex.z-dn.net/?f=1%5C%20%7C%5C%201%5C%20%5C%202%5C%20%5C%20-3%5C%20%5C%203)
![3](https://tex.z-dn.net/?f=3)
--------------------------------
![|\ 1\ \ 3\ \ \ 0](https://tex.z-dn.net/?f=%7C%5C%201%5C%20%5C%203%5C%20%5C%20%5C%200)
Multiply that 0 by the divisor (1) i.e. ![1 * 0 = 0](https://tex.z-dn.net/?f=1%20%2A%200%20%3D%200)
Write down the result under the next digit i.e. (under 3)
![1\ |\ 1\ \ 2\ \ -3\ \ 3](https://tex.z-dn.net/?f=1%5C%20%7C%5C%201%5C%20%5C%202%5C%20%5C%20-3%5C%20%5C%203)
![0](https://tex.z-dn.net/?f=0)
--------------------------------
![|\ 1\ \ 3\ \ \ 0](https://tex.z-dn.net/?f=%7C%5C%201%5C%20%5C%203%5C%20%5C%20%5C%200)
Sum 3 and 0 i.e ![3 + 0 = 3](https://tex.z-dn.net/?f=3%20%2B%200%20%3D%203)
Since there is no other computation to do, the result of the last sum is the remainder.
So:
![Remainder = 3](https://tex.z-dn.net/?f=Remainder%20%3D%203)